2020
DOI: 10.3390/ijms21249594
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Soybean-Derived Lunasin in Wheat and Assessment of Its Anti-Proliferative Activity in Colorectal Cancer HT-29 Cells

Abstract: Lunasin is a soybean-derived peptide that exhibits anticancer bioactivity in different cancer cells and has been identified in different plants. However, recent studies revealed through molecular and chemical analyses that lunasin was absent in wheat and other cereals. In this study, the soybean-derived lunasin was cloned into pCAMBIA3300 and we transferred the expression vector into wheat via an Agrobacterium-mediated transformation. The identification of transgenic wheat was detected by polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Moreover, Choi et al have indicated that vorinostat can inhibit the expression of IL-6 and IL-8 in peripheral blood mononuclear cells (PBMCs) from treated patients [ 45 ]. In our previous study, lunasin of transgenic wheat also had inhibitory effect on colon cancer cells by modulating the apoptosis pathway, and the expression of Bax and caspase3 was increased while Bcl-2 was decreased [ 46 ]. Furthermore, TNF-α, VEGFA, and c-Myc were considered to serve important roles in tumorigenesis and tumor development, which can be regulated by HDAC1 [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Choi et al have indicated that vorinostat can inhibit the expression of IL-6 and IL-8 in peripheral blood mononuclear cells (PBMCs) from treated patients [ 45 ]. In our previous study, lunasin of transgenic wheat also had inhibitory effect on colon cancer cells by modulating the apoptosis pathway, and the expression of Bax and caspase3 was increased while Bcl-2 was decreased [ 46 ]. Furthermore, TNF-α, VEGFA, and c-Myc were considered to serve important roles in tumorigenesis and tumor development, which can be regulated by HDAC1 [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that Lunasin activated caspase‐3 and cleaved PARP could modulate the progression of the cell cycle progression mediated by the cyclin‐dependent kinase inhibitor p21. Similarly, Lunasin exerted antiproliferative activity by regulating the apoptosis pathway of HT‐29 human colon adenocarcinoma cells (Fan et al, 2020). On the other hand, González‐Montoya et al (2018) studied peptides from a soybean sprout protein isolate and found that fractions >10, 5–10, and <5 kDa caused cytotoxicity to Caco‐2, HT‐29, and HCT116 human colon cancer cells.…”
Section: Biological Activities Related To Gastrointestinal Digestion ...mentioning
confidence: 99%
“…Lunasin was a unique 43-amino-acid cancer prevention peptide, which binded closely to deacetylated histone, destroying the kinetics of histone acetylation-deacetylation and leading to cell death, but this only occurred in transforming cells and does not affect normal cells. The polypeptide extracted from transgenic wheat had higher anticancer activity ( 81 83 ).…”
Section: The Biological Activity Of Wheat Germ Peptidesmentioning
confidence: 99%